Natural and synthetic isoprene rubbers obtained using Ziegler–Natta catalysts - A. A. Zuev; V. L. Zolotarev; I. P. Levenberg; L. A. Kovaleva; I. Sh. Nasyrov (Тонкие химические технологии, 2024)
Objectives. To compare the properties of rubber compounds and rubbers based on natural rubber RSS1 and synthetic isoprene rubbers obtained using Ti, Nd, Gd catalysts, both when used individually in the formulation of rubber compounds and when synthetic analogues partially replace natural rubber.Methods. Rubber compounds were prepared using a laboratory roll and a 100 cm3 rubber mixer. For rubber compounds, the following factors were determined: Mooney viscosity, cohesive strength, and vulcanization characteristics. For rubbers, the following factors were determined: physical and mechanical parameters, Shore A hardness, rebound resilience, and volume loss upon abrasion.Results. Based on the results of the rubber compound tests, the study showed that compounds based on all the synthetic polyisoprenes studied are significantly inferior to compounds based on natural rubber in terms of cohesive strength. The partial replacement of natural rubber with synthetic rubber (regardless of the type of catalytic system) leads to a significant decrease in the cohesive strength of the blends. Despite the differences observed in the properties of the rubber compounds, the results of the rubbers based on individual rubbers do not manifest significant differences.Conclusions. The study demonstrated the influence of defects (oligomers, gel, low molecular weight fractions, branches, and 3,4-units) in the structure of synthetic polyisoprenes on the cohesive strength index of rubber compounds based on them, in which the number of 3,4-units plays a decisive role. The study also showed the potential of studying synthetic polyisoprenes as analogues of natural rubber in formulations of rubber compounds in the aims of resolving the problem of import substitution in the tire and rubber goods industry.